2020
DOI: 10.18502/jovr.v15i1.5954
|View full text |Cite
|
Sign up to set email alerts
|

Vogt-Koyanagi-Harada with Unilateral Clinical Presentation: A Case Report

Abstract: Purpose: To report a case of acute Vogt-Koyanagi-Harada (VKH) disease with unilateral clinical manifestations followed by late fellow eye involvement. Case Report: This case report reviews the 12-month follow-up observation of a 44-year old woman who presented to the emergency department with unilateral progressive and painless visual blurring. Ophthalmoscopic findings, best-corrected visual acuity (BCVA), fluorescein angiography (FAG), enhanced-depth optical coherence tomography (EDIOCT), indocyanine gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Typically, VKH is a systemic granulomatous disease with bilateral ocular involvement. However, previous studies reported some cases of VKH with a unilateral presentation 8,9 . The main challenge in this patient is the lack of evidence of inflammation such as papillitis, vitreous haziness, and anterior segment inflammation.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Typically, VKH is a systemic granulomatous disease with bilateral ocular involvement. However, previous studies reported some cases of VKH with a unilateral presentation 8,9 . The main challenge in this patient is the lack of evidence of inflammation such as papillitis, vitreous haziness, and anterior segment inflammation.…”
Section: Discussionmentioning
confidence: 84%
“…However, previous studies reported some cases of VKH with a unilateral presentation. 8 , 9 The main challenge in this patient is the lack of evidence of inflammation such as papillitis, vitreous haziness, and anterior segment inflammation. Besides, he overused marijuana.…”
Section: Discussionmentioning
confidence: 99%
“…The latter eye therefore never developed clinically apparent disease. In the “unilateral” cases reported, two patients were investigated by ICGA that showed bilateral ICGA signs, one of which showed discreet signs in the apparently uninvolved eye before full-blown ICGA signs appeared 2 months later [ 27 ]. An interesting report showed delayed involvement of the second eye after the first eye showed VKH signs [ 28 ].…”
Section: Discussionmentioning
confidence: 99%